2001
DOI: 10.1016/s0014-5793(01)02385-7
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine 331 and phenylalanine 334 in Clostridium perfringens α‐toxin are essential for cytotoxic activity

Abstract: Differences in the biological properties of the Clostridium perfringens phospholipase C (K K-toxin) and the C. bifermentans phospholipase C (Cbp) have been attributed to differences in their carboxy-terminal domains. Three residues in the carboxy-terminal domain of K K-toxin, which have been proposed to play a role in membrane recognition (D 269

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
(73 reference statements)
0
14
0
1
Order By: Relevance
“…Despite the recent identification of the residues critical for toxicity in Cp-PLC (24,43,44), the molecular mechanism of action of this toxin is still not completely understood. Cp-PLC is hemolytic, necrotizing, lethal, and highly toxic to various cell types, particularly those that are deficient in UDPGlc (18).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent identification of the residues critical for toxicity in Cp-PLC (24,43,44), the molecular mechanism of action of this toxin is still not completely understood. Cp-PLC is hemolytic, necrotizing, lethal, and highly toxic to various cell types, particularly those that are deficient in UDPGlc (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study showed that residues which correspond to D293, D305, and K330 are conserved in Csp and/or Cbp, suggesting that other residues may be required for the strong biological activities of Cpa. AlapeGiron et al (1) reported that D269, Y275, Y307, Y331, and D336 of Cpa were critical for toxicity, and Jepson et al (11) reported that Y331 and F334 of Cpa were essential for it. Among the six residues, those that correspond to Y307 and D336 are conserved in both Csp and Cbp but those that correspond to D269, Y275, Y331, and F334 are substituted for Y, N, R, and I, respectively, in Csp and Y, N, Y, and I, respectively, in Cbp.…”
Section: Discussionmentioning
confidence: 99%
“…Among the six residues, those that correspond to Y307 and D336 are conserved in both Csp and Cbp but those that correspond to D269, Y275, Y331, and F334 are substituted for Y, N, R, and I, respectively, in Csp and Y, N, Y, and I, respectively, in Cbp. As discussed in the literature on the subject (1,11), amino acid residues which are specific to Cpa and not to other nontoxic phospholipases should be responsible for the toxicity. The C-terminal domain of Cpa possesses three calcium-binding sites, termed Ca1 (E32, D269, E271, D336, and A337), Ca2 (D293, N294, G296, and D298), and Ca3 (T272, D273, N297, and D298) (21).…”
Section: Discussionmentioning
confidence: 99%
“…We also reported that the C-terminal region contributes to the activities of the alpha-toxin (9). Jepson et al (4) reported that the C-terminal domains of alpha-toxin and CbPLC are responsible for the differences in activity of these proteins. Guillouard et al (1) showed that Asp-269 and Asp-336 in alpha-toxin are involved in the binding to Ca 2 which is essential for hemolytic activity.…”
mentioning
confidence: 99%